Forest Law and Sustainable Development : Addressing Contemporary Challenges Through Legal Reform - Christy, Lawrence C.; Di Leva, Charles E.; Lindsay, Jonathan M.; Takoukam, Patrice Talla (Washington, DC : World Bank, 2012)
This study is intended to be a systematic and practical guide to the basic features of modern forestry legislation. It identifies a range of issues that should be considered in assessing the adequacy of forest laws and presents options for addressing those issues in ways that may improve the effectiveness of law as a foundation for sustainable forest management. Part One locates forestry law within the wider legal framework, exploring its complex interrelations with other sectoral and general laws. Land issues are given special treatment because the relationship between forest access and use and land tenure is so important. Part Two explores in detail the legal treatment of core forest management issues, such as forest classification, planning, concessions, licensing, and private forest management. Part Three focuses on the role of national and sub-national institutions in the sustainable management of forest resources. As decentralization of forestry responsibilities and devolution of powers are growing, local actors are given more prominent roles in forest planning, use, and management, through such means as community-based arrangements. Part Four explores a range of environmental and trade issues. Part Five examines financial and enforcement measures, emphasizing that compliance and enforcement of forest law should be reinforced by financial and administrative sanctions. The study concludes with some reflections on how the effectiveness of forest law can be enhanced by attention to the principles that guide the process of drafting.